MIRAGRODEP-AEZ 1.0: Documentation - Bouët, Antoine; Laborde Debucquet, David; Traoré, Fousseini (International Food Policy Research Institute, 2022)
MIRAGRODEP-AEZ is a recursive dynamic multi-region, multi-sector Computable General Equilibrium (CGE) model based on MIRAGRODEP which in turn is based on MIRAGE (Modelling International Relations Under Applied General Equilibrium) with Agro-ecological zones (regions). It constitutes an extension of the MIRAGRODEP model that allows the user to perform analysis at the subnational level using spatial disaggregated data. The model is particularly suitable for agricultural policy analysis that require working at different levels of disaggregation to consider differences in agro-ecological conditions.